The causal relationship between eosinophil counts and hepatocellular carcinoma in East Asians: evidence from a Mendelian randomization study - Dong Liu; Jinju Xia; Ruilin He; Ronghua Zhu (Discover Oncology)
Abstract Objectives To investigate the causal relationship between the genetically predicted eosinophil counts and hepatocellular carcinoma (HCC) in East Asians. Additionally, we aimed to explore the infiltration and clinical impact of eosinophils in HCC using the Gene Expression Profiling Interactive Analysis (GEPIA). Methods We utilized a discovery set to explore the correlation between eosinophil counts and HCC, and validated the findings using a validation set. We employed multivariate mendelian randomization (MR) analysis to exclude confounding factors. The results from the discovery set and the validation set were combined through meta-analysis. The GEPIA online platform was utilized to analyze the infiltration and clinical impact of eosinophils in HCC. Results The genetically predicted counts of eosinophils were associated with a reduced risk of HCC, with meta-analysis yielding an OR of 0.662 (95% CI: 0.532–0.823). The eosinophil infiltration was significantly lower in HCC tissue compared to normal liver tissue (F = 4.90, P = 0.03), and the survival outcomes were not affected by the level of eosinophil infiltration. Conclusion Our findings indicate a potential causal link between lower eosinophil counts and the occurrence of HCC in the East Asian population, offering valuable insights into the prevention and understanding of HCC.